2012
DOI: 10.7326/0003-4819-156-7-201204030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an iPod Video Intervention on Consent to Donate Organs

Abstract: Background The gap between the supply of organs available for transplantation and demand is growing, especially among ethnic groups. Objective To evaluate the effect of a video designed to address concerns of ethnic groups about organ donation. Design Cluster randomized, controlled trial. Randomization was performed by using a random-number table with centralized allocation concealment. Participants and investigators assessing outcomes were not blinded to group assignment. (ClinicalTrials.gov registration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 23 publications
2
72
0
Order By: Relevance
“…24 The rates of consent for organ donation in the intervention and control arms compared favorably to that of other studies, 2 but were lower than those seen when the same video was shown to individuals applying for their first driver's license at the bureau of motor vehicles. 1 One potential reason for the difference was the disparate study populations. This study population was older, had existing medical conditions, and was more likely to be minority-all potential barriers to consent for organ donation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…24 The rates of consent for organ donation in the intervention and control arms compared favorably to that of other studies, 2 but were lower than those seen when the same video was shown to individuals applying for their first driver's license at the bureau of motor vehicles. 1 One potential reason for the difference was the disparate study populations. This study population was older, had existing medical conditions, and was more likely to be minority-all potential barriers to consent for organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this proportion is less than the 39 % who declined to participate in a prior randomized controlled trial of organ donation. 1 About one-sixth of control patients discussed organ donation with their providers and signed up to become organ donors. Thus, it appears that simply participating in an organ donation study (without the video or cueing interventions) was sufficient to encourage some patients to have discussions and sign up to be donors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations